Well-Being Science for Teaching and the General Public. (September 2022) - Tov, William; Wirtz, Derrick; Kushlev, Kostadin; Biswas-Diener, Robert; Diener, Ed
Research on well-being has exploded in recent years to more than 55, 000 relevant publications annually, making it difficult for psychologists—including key communicators such as textbook authors—to stay current with this field. Moreover, well-being is a daily concern among policymakers and members of the general public. Well-being science is relevant to the lives of students—illustrating the diverse methods used in the behavioral sciences, presenting highly replicated findings, and demonstrating the diversity of individuals and cultures. Therefore, in this article, we present eight major findings that teachers and authors should seriously consider in their coverage of this field. These topics include processes such as adaptation, influences such as income, the benefits of well-being, and cultural and societal diversity in well-being and its causes. We also examine how much these topics were covered in 15 of the most popular introductory psychology textbooks. Although some topics such as social relationships and well-being were discussed in nearly all textbooks, others were less frequently covered, including the validity of self-reported well-being, the effects of spending on happiness, and the impact of culture and society on well-being. We aim to ensure more complete coverage of this important area in psychology courses.